Mathematical Verification for Transmission Performance of Centralized Lightwave WDM-RoF-PON with Quintuple Services Integrated in Each Wavelength Channel. (29th December 2015) - Chen, Shuai; Nai, Wei; Zhang, Fangqi; Wang, Shaoyin; Dong, Decun; Yu, Yi
Abstract : Wavelength-division-multiplexing passive-optical-network (WDM-PON) has been recognized as a promising solution of the "last mile" access as well as multibroadband data services access for end users, and WDM-RoF-PON, which employs radio-over-fiber (RoF) technique in WDM-PON, is even a more attractive approach for future broadband fiber and wireless access for its strong availability of centralized multiservices transmission operation and its transparency for bandwidth and signal modulation formats. As for multiservices development in WDM-RoF-PON, various system designs have been reported and verified via simulation or experiment till now, and the scheme with multiservices transmitted in each single wavelength channel is believed as the one that has the highest bandwidth efficiency; however, the corresponding mathematical verification is still hard to be found in state-of-the-art literature. In this paper, system design and data transmission performance of a quintuple services integrated WDM-RoF-PON which jointly employs carrier multiplexing and orthogonal modulation techniques, have been theoretically analyzed and verified in detail; moreover, the system design has been duplicated and verified experimentally and the theory system of such WDM-RoF-PON scheme has thus been formed.